Weak Type Estimates for Intrinsic Square Functions on Weighted Morrey Spaces (Analysis in Theory and Applications, 2013)
In this paper, we will obtain the weak type estimates of intrinsic square functions including the Lusin area integral, Littlewood-Paley $g$-function and $g^*_λ$-function on the weighted Morrey spaces $L^{1,κ}(w)$ for $0
Keywords: Intrinsic square function; weighted Morrey space; $A_p$ weight.